ZnS and CdS counterparts of biphenylene lattice: A density functional theory prediction - Laranjeira, José A.S. [UNESP]; Abdullahi, Yusuf Z.; Ersan, Fatih; Sambrano, Julio R. [UNESP] (Elsevier, 2024)
This study presents four novel inorganic structures based on the biphenylene network (BPN): planar BPN-ZnS (p-BPN-ZnS) and BPN-CdS (p-BPN-CdS) and buckled BPN-ZnS (b-BPN-ZnS) and BPN-CdS (b-BPN-CdS). Cohesive energy analyses reveal that structural buckling enhances stability, and a perturbation is necessary to obtain planar lattices. Phonon dispersion and ab initio molecular dynamics (AIMD) simulations demonstrated the dynamical and thermal stabilities. ZnS-based structures exhibited more pronounced charge accumulation and depletion than CdS. All evaluated structures are ultra-wideband gap semiconductors, with band gap energy values of 4.33, 5.34, 3.59, and 4.30 eV (at HSE06 level) for p-BPN-ZnS, b-BPN-ZnS, p-BPN-CdS, and b-BPN-CdS, respectively. p-BPN-ZnS demonstrated the highest Young modulus (Yx/Yy = 25.295/34.874 N/m), followed by p-BPN-CdS (Yx/Yy = 15.286/21.339 N/m). On the other hand, b-BPN-ZnS and b-BPN-CdS exhibit lower Young Modulus, Yx/Yy = 4.135/14.709 and 11.842/8.218 N/m, respectively. Notably, b-BPN-ZnS displayed a particular characteristic, a negative Poisson ratio (νx/νy = -0.008/-0.030), being an auxetic material. This report is expected to stimulate both theoretical and experimental researchers in the prediction and development of new inorganic materials based on the biphenylene network.
Keywords: Auxetic; Biphenylene; BPN; CdS; DFT; ZnS